(untitled) (Research, Society and Development, 2021)
Objective: to verify how income generation strategies and therapeutic workshops favor user citizenship in the social inclusion process. Methodology: Study with an exploratory qualitative approach. Data collection took place in a Psychosocial Care Center in the cities of Crato and Juazeiro do Norte, Ceará. The study population was 20 mental health professionals: psychologists, nurses, nursing technicians, social workers, pharmacist, occupational therapist and psychopedagogist. The interviews were conducted from August to December 2018. A semi-structured interview script was used, descriptively analyzed and submitted to a Multimethod Analysis methodology, organized in a prepared folder and processed in the Iramuteq software. Results: The Descending Hierarchical Classification method was applied and 7 classes were obtained. Class 7 has the largest representation (20%) of the corpus. The factorial representation shows that classes 3,7 and 6 refer to the types of activities that are developed. Classes 3, 7 and 6 evidenced the income generation workshops. A c 5 and a 2 highlight the importance of encouraging and marketing the products that are produced. Grade 4 interlinked with grade 3 the importance of family participation and grades 1 and 6 empowerment. Conclusion: They point to the need for greater participation of family members in activities AND reflection on the potential that can come from the solidarity economy and occupational therapy, to elucidate and strengthen new possibilities for proposing inclusive work in the field of mental health.